Detailed National Accounts, SNA 2008: Final consumption expenditure of households (Edition 2015) (OECD National Accounts Statistics, 2008)
This comparative table includes statistics on the final consumption expenditure of households broken down by the COICOP (Classification of Individual Consumption According to Purpose) classification and by durability. Final consumption expenditures comprise different variables such as clothing and footwear, health, food expenditure, transport, education, durable goods, final consumption expenditure, social protection and more. Data are internationally comparable by following the System of National Accounts 1993 (SNA 1993) and are expressed in millions of national currency. Data are presented from 1950 onwards